2013
DOI: 10.1016/j.bcp.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

IκB kinase ɛ (IKKɛ): A therapeutic target in inflammation and cancer

Abstract: The innate immune system forms our first line of defense against invading pathogens and relies for a major part on the activation of two transcription factors, NF-κB and IRF3. Signaling pathways that activate these transcription factors are intertwined at the level of the canonical IκB kinases (IKKα, IKKβ) and non-canonical IKK-related kinases (IKKε, TBK1). Recently, significant progress has been made in understanding the function and mechanism of action of IKKε in immune signaling. In addition, IKKε impacts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 91 publications
(129 reference statements)
1
62
0
3
Order By: Relevance
“…The mutual interplay between NF-κB and proinflammatory cytokines such as TNFα and IL1β might stimulate cancer cell proliferation during chronic inflammation [70]. Inhibition of NF-κB with IKK inhibitors, siRNA, or IkappaB super suppressor downregulated lung cancer cell survival and proliferation [70,71].…”
Section: Roles Of Inflammation In Bio-behaviors Of Lung Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutual interplay between NF-κB and proinflammatory cytokines such as TNFα and IL1β might stimulate cancer cell proliferation during chronic inflammation [70]. Inhibition of NF-κB with IKK inhibitors, siRNA, or IkappaB super suppressor downregulated lung cancer cell survival and proliferation [70,71].…”
Section: Roles Of Inflammation In Bio-behaviors Of Lung Cancer Cellsmentioning
confidence: 99%
“…Inhibition of NF-κB with IKK inhibitors, siRNA, or IkappaB super suppressor downregulated lung cancer cell survival and proliferation [70,71]. IL6 is considered as a key growth-promoting and anti-apoptotic factor to promote cell proliferation in primary squamous cell carcinomas, adenocarcinomas, or tumor cell lines [72].…”
Section: Roles Of Inflammation In Bio-behaviors Of Lung Cancer Cellsmentioning
confidence: 99%
“…Activation of this transcription factor is a very important step in the development of DN [26]; therefore, the pharmacological modulation of this process is the main objective in the design of new therapies for DN. In this work, we analyzed the effects of the natural compound parthenolide, which is an NF-κB inhibitor, and found that it reduces IκB degradation, preventing NF-κB activation and subsequent MCP-1 mRNA and protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive basic and clinical research over the past 40 years, little progress has been made in treating SCLC [64]. The innate immune system forms our first line of defense against invading pathogens and relies for a major part on the activation of two transcription factors, NF-κB and interferon regulatory factor 3 (IRF3) [65]. NF-κB-dependent cell survival genes play an important antiapoptotic role [66].…”
Section: Smoking and Copdmentioning
confidence: 99%